2022
DOI: 10.3389/fimmu.2022.947187
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody responses before and after a third dose of the BNT162b2 vaccine in Italian healthcare workers aged ≤60 years: One year of surveillance

Abstract: This study monitored the anti-spike-receptor-binding domain (RBD) and neutralizing antibodies induced by the Pfizer/BioNTech mRNA BNT162b2 vaccine in a cohort of 163 healthcare workers aged ≤60 years. We have taken advantage of two study groups, both of whom received the first two doses in the same time window, but Group 1 (54 HCWs) received the third dose 2 months before Group 2 (68 HCWs) did. The cohorts were monitored from the 12th day after the first vaccine dose up to 1 month after the third vaccine dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Notably, RBD-nanoparticle immunizations in pre-immunized NHPs elicited high overall ELISA and neutralization titers against a diverse array of both matched and mismatched sarbecoviruses (Figure 2B-C; Figure S2B-C). As generally observed for vaccines, 2931 we found that elicited Ab binding responses contracted after both RBD-nanoparticle and bivalent repRNA immunizations (5-8 fold from week 2 to week 8) and after boosting (∼10 fold from week 10 to week 22). Contractions in binding Ab levels largely correlated with drops in neutralizing Ab titers (Figure 2B-C; Figure S2B-C).…”
Section: Resultssupporting
confidence: 81%
“…Notably, RBD-nanoparticle immunizations in pre-immunized NHPs elicited high overall ELISA and neutralization titers against a diverse array of both matched and mismatched sarbecoviruses (Figure 2B-C; Figure S2B-C). As generally observed for vaccines, 2931 we found that elicited Ab binding responses contracted after both RBD-nanoparticle and bivalent repRNA immunizations (5-8 fold from week 2 to week 8) and after boosting (∼10 fold from week 10 to week 22). Contractions in binding Ab levels largely correlated with drops in neutralizing Ab titers (Figure 2B-C; Figure S2B-C).…”
Section: Resultssupporting
confidence: 81%
“…Even after two doses of a COVID-19 vaccine, patients with cancer have lower total antibody geometric mean titers (GMTs) than healthy adults, and the immune response decreases around 6 months following vaccination [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Central to the vaccine-elicited immune response are neutralizing antibodies, which have also been shown to decrease and be insufficient following only two vaccine doses in cancer patients [ 11 , 12 , 13 ]. The benefit of the third vaccine dose for at-risk populations has been shown via an increase in total antibody GMT [ 2 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%